Penerapan Nilai-Nilai Moderasi Beragama pada Anak Usia Dini dalam Keluarga - Fajriyah, Lathifatul; Riswandi, Fitta Nurisma (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This study aims to determine how to apply the values ​​of religious moderation in early childhood. The method used in this research is qualitative with a library research approach. This research is used to solve problems by using data from several journals and books to draw conclusions. The results of this study are the values ​​of moderation are very important to be taught in early childhood, especially in the family, because the family is a central role in the growth and development of children. teaching religious moderation in the family can be done in daily activities. The values ​​of religious moderation that must be taught to children include balance (Tawazun), justice (‘Adalah), tolerance (Tasamuh), taking the middle way (Tawassuth) and Deliberation (Syura). These values ​​if implemented are mutual respect and respect, compassion, cooperation and mutual help, fairness, peace, tolerance, living in harmony, caring and sympathetic towards something. Applying the values ​​of religious moderation in the family can use several methods, namely example, habituation, advice and storytelling.